2013
DOI: 10.1002/2013jg002388
|View full text |Cite
|
Sign up to set email alerts
|

Improved assessment of gross and net primary productivity of Canada's landmass

Abstract: [1] We assess Canada's gross primary productivity (GPP) and net primary productivity (NPP) using boreal ecosystem productivity simulator (BEPS) at 250 m spatial resolution with improved input parameter and driver fields and phenology and nutrient release parameterization schemes. BEPS is a process-based two-leaf enzyme kinetic terrestrial ecosystem model designed to simulate energy, water, and carbon (C) fluxes using spatial data sets of meteorology, remotely sensed land surface variables, soil properties, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 94 publications
5
46
1
Order By: Relevance
“…Finally, although assessing IBIS was not the point of this study and has already been done elsewhere (Foley et al, 1996;Delire and Foley, 1999;Kucharik et al, 2000Kucharik et al, , 2006Lenters et al, 2000;El Maayar et al, 2001, the results obtained for the three grid cells compared favourably to recent studies, with a small underestimation of biomass (Beaudoin et al, 2014) and NPP (Gonsamo et al, 2013). Obtaining reliable data on soil carbon is notoriously difficult; when compared to the Harmonized World Soil Database (down to a depth of 1 m) as provided by Exbrayat et al (2014), IBIS apparently overestimated soil carbon (down to a depth of 4 m), at least in the southern grid cell, even when accounting for the fact that a substantial fraction of soil carbon is found at a depth greater than 1 m (Jobbágy and Jackson, 2000).…”
Section: Evaluation Of Performancesupporting
confidence: 66%
“…Finally, although assessing IBIS was not the point of this study and has already been done elsewhere (Foley et al, 1996;Delire and Foley, 1999;Kucharik et al, 2000Kucharik et al, , 2006Lenters et al, 2000;El Maayar et al, 2001, the results obtained for the three grid cells compared favourably to recent studies, with a small underestimation of biomass (Beaudoin et al, 2014) and NPP (Gonsamo et al, 2013). Obtaining reliable data on soil carbon is notoriously difficult; when compared to the Harmonized World Soil Database (down to a depth of 1 m) as provided by Exbrayat et al (2014), IBIS apparently overestimated soil carbon (down to a depth of 4 m), at least in the southern grid cell, even when accounting for the fact that a substantial fraction of soil carbon is found at a depth greater than 1 m (Jobbágy and Jackson, 2000).…”
Section: Evaluation Of Performancesupporting
confidence: 66%
“…Our GPP estimate for Canada's landmass is 45.6% higher than a recent estimate (2.68 Pg C yr −1 ) based on an ecosystem model (Gonsamo et al, 2013). Evergreen forests had the highest contribution to Canada's annual GPP, ER, and NEP; mixed forests, shrublands, and croplands had intermediate contributions; deciduous forests, savannas, and grasslands had the lowest values (Fig.…”
Section: Annual Gpp Er and Nep Of The Us And Canadacontrasting
confidence: 64%
“…Several intermodel comparisons and site‐level validations have shown that BEPS can produce reasonable GPP and ET estimates (Amthor et al, ; Grant et al, ; Liu et al, ; Potter et al, ). Its usage has expanded from boreal ecosystems to other plant functional types in the past decade (Chen et al, ; Gonsamo et al, ; Wang et al, ), and BEPS has been updated to support simulations at hourly and half‐hourly steps (Chen et al, ).…”
Section: Methodsmentioning
confidence: 99%